PEMANFAATAN BUDAYA LOKAL DALAM PEMBELAJARAN MATEMATIKA MELALUI MEDIA SCRAPBOOK UNTUK MENINGKATKAN LITERASI MATEMATIKA SISWA DI SLB SWASTA OSAKALI ASAHAN - Anim, Anim; Permatasari, Putri Lidiana; Sirait, Syahriani; Manulang, Muhammad Tuah Anggana; Iona, Bella Norma (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: This article discusses the introduction of local culture in mathematics learning,designed in the form of a scrapbook media, to enhance mathematical literacy skills of students at SLB Swasta Osakali, focusing on flat shapes material. The scrapbook media is designed to link the learning material with local cultural elements familiar to the students, aiming to strengthen mathematical literacy. This service is specifically conducted for students with hearing impairments to observe changes in mathematical literacy skills before and after the implementation of the scrapbook, as well as to evaluate its effectiveness in stimulating students' mathematical literacy. The method used in this activity is a training approach, which includes the dissemination of the material, demonstration of scrapbook media usage, and training skills to relate mathematical concepts to local culture. A quasi-experimental approach with a pretest-posttest design is also applied to measure the improvement in students' mathematical literacy. The target group consists of 9 senior high school students with hearing impairments at SLB Swasta Osakali Asahan, assisted by class teachers as communication intermediaries. Evaluation is conducted at the end of the training by distributing questionnaires to assess participants' understanding of the material and the scrapbook media. The evaluation results show that all students demonstrated improved knowledge, both from individual questionnaire calculations and students' participation and enthusiasm during the scrapbook activity. Thus, the use of scrapbook media based on local culture can be an innovative strategy in inclusive education for children with special needs. Keywords: mathematical literacy; local culture; scrapbook media; inclusive education. Abstrak: Artikel ini membahas pengenalan budaya lokal dalam pembelajaran matematika yang dirancang dalam bentuk media scrapbook untuk meningkatkan kemampuan literasi matematika siswa di SLB Swasta Osakali, pada materi bangun datar. Media scrapbook ini dirancang untuk mengaitkan materi pembelajaran dengan elemen budaya lokal yang dikenal oleh siswa, guna memperkuat literasi matematika. Pengabdian ini difokuskan pada siswa penyandang tunarungu untuk menganalisis perubahan kemampuan literasi matematika sebelum dan sesudah penerapan scrapbook, serta mengevaluasi dampaknya. Metode yang digunakan adalah pelatihan yang meliputi penyuluhan substansi materi, demonstrasi penggunaan media scrapbook, serta pelatihan keterampilan mengaitkan konsep matematika dengan budaya lokal. Pendekatan kuasi eksperimen dengan desain pretest-posttest juga diterapkan untuk mengukur peningkatan kemampuan literasi matematika siswa. Target pelatihan adalah 9 siswa tunarungu tingkat SMA di SLB Swasta Osakali Asahan, yang didampingi oleh guru kelas sebagai perantara komunikasi. Evaluasi dilakukan dengan menyebarkan kuesioner untuk mengukur pemahaman peserta terhadap materi dan media scrapbook. Hasil evaluasi menunjukkan bahwa seluruh siswa mengalami peningkatan pengetahuan, dilihat dari skor kuesioner dan antusiasme siswa selama pelatihan. Dengan demikian, penggunaan media scrapbook berbasis budaya lokal dapat menjadi strategi inovatif dalam pendidikan inklusif untuk anak berkebutuhan khusus. Kata kunci: literasi matematika, budaya lokal, media scrapbook, pendidikan inklusif.